Imaging of COVID-19: Experience in BIRDEM General Hospital - Taher, MA; Sultana, Jafreen; Behnom, Ishtiaque Mohammad; Saha, Mohua (BIRDEM Medical Journal, 2020)
Background: Pneumonia associated with the coronavirus disease 2019 (COVID-19) emerged in Wuhan of China which was recognized as a global health emergency. Role of imaging, specially high resolution computed tomography (HRCT) of chest is considered as an important tool in the early diagnosis, evaluation of disease progression and prompt management of COVID-19 patient in this global health pandemic. This study was designed to report the spectrum of HRCT imaging findings in COVID-19 infected patients. Methods: This cross-sectional study included 30 consecutive reverse transcriptase polymerase chain reaction (RT-PCR) positive COVID-19 patients who underwent HRCT chest from 1st of September 2020 to 30th October 2020 in BIRDEM General Hospital. Dhaka, Bangladesh. Prevalence, distribution, extent and type of abnormal lung findings were recorded. Results: Total 30 patients diagnosed with COVID-19 were included. Among them, 26 (86.6%) patients had fever and 17 (66.66%) patients had fatigability. The most frequent CT abnormality was ground glass opacity in (26, 86.67%). Crazy-paving pattern was found in 19 (63.33%) cases. Most patients had multiple lesions and involved all the 5 lobes The lesions were mostly peripheral (26, 86.6%) in distribution. Most commonly involved lobe is right lower lobe (27, 90%). Conclusion: Radiology & Imaging, specially HRCT of chest is an excellent modality in diagnosis of disease, evaluation of progression of disease, evaluation of post COVID-19 patient and prompt management of COVID- 19 patient in this global health emergency. Birdem Med J 2020; 10, COVID Supplement: 56-62